Carbon Accounting and Corporate Sustainability: Bibliometric Insights from 2010–2025 - Judijanto, Loso; Reza, Fahry; Indrawati, Mos; Kristanto, Eri; Sudarmanto, Eko (Westscience Press, 2025)
This study offers a thorough bibliometric review of studies concerning carbon accounting and business sustainability published from 2010 to 2025. Publications were studied using Scopus as the primary database, employing Bibliometrix (R) and VOSviewer to investigate publishing trends, prominent authors, institutions, and countries, alongside co-authorship, co-citation, and keyword co-occurrence networks. The results indicate that carbon accounting, sustainable development, climate change, environmental impact, and greenhouse gas emissions form the fundamental theme framework of the discipline. Emerging domains encompass carbon neutrality, carbon economy, supply-chain emissions, energy efficiency, and artificial intelligence, indicating a transition towards technology-driven and sector-specific decarbonization approaches. International collaboration networks are extensive and worldwide, with the United Kingdom, United States, Australia, China, and Germany serving as primary hubs, but author and affiliation networks are more disjointed. The study enhances theoretical comprehension of carbon accounting as a cohesive component of climate governance and provides practical recommendations for regulators and practitioners aiming to develop more effective reporting systems and decarbonization strategies.